To generate greater economic benefits from visiting ships : to develop Singapore into a steel products HUB - Ng, Janson Jin Yuan (2017)
This paper focuses on investigating the approach of developing Singapore into a steel products hub to generate greater economic benefits from visiting ships to the Port of Singapore. The main driver for this paper is due to the increase competition among ports, amidst the weak shipping cycle. The above topic is selected due to the lack of development relative to the other sectors and the high potential of creating benefits to the Singapore economy. The paper will discussed the feasibility of developing Singapore into a steel products hub through a series of analysis. The paper will be broken down into four parts. First, the different dry bulk commodities are examined to narrow down on the ones that are feasible to conduct business in, which is found out to be steel. Secondly, a thorough study on the steel industry will be conducted to understand the practices and processes of the steel business. Third, the different factors affecting the feasibility of developing the steel hub in Singapore are evaluated. Possible economic benefits are explored to weigh the cost and benefits of the idea. Last but not least, recommendations are presented to improve on the steel sector in the Port of Singapore. These recommendations are inspired from practices in the other sectors and industries, which have similarity in the operations of the steel sector.